Importance of herpes viruses in children with post-COVID conditions - M.S. Savenkova; I.A. Sotnikov; A.A. Afanasieva; Ya.V. Afanasieva; R.V. Dushkin (LCC «Medicine-Inform», 2023)
M.S. Savenkova1,2, I.A. Sotnikov2, A.A. Afanasieva1,2, Ya.V. Afanasieva3, R.V. Dushkin4 1Pirogov Russian National Research Medical University, Moscow, Russian Federation 2Morozov Children's City Clinical Hospital, Moscow, Russian Federation 3All-Russian Public Organization "Russian Academy of Engineering", Moscow, Russian Federation 4LLC "Agency of Artificial Intelligence," Moscow, Russian Federation Aim: to assess the prevalence of detection of confirmed herpes virus infections (HVI) in children who had a previous COVID-19 infection, characterize specific clinical manifestations of the disease under the new conditions (post-COVID syndrome), and to provide a rationale for the administration of drug therapy. Patients and Methods: of 456 patients who received medical consultations from September 2021 to July 2022, the authors selected 72 (15.8%) children (42 boys and 30 girls) who had a previous SARS-CoV-2 infection confirmed by serological tests or polymerase chain reaction and in whom herpes viruses were found during serological evaluation. Results: most of the children (81.4%) visited the polyclinic within the first six months after the COVID-19 infection. Epstein-Barr virus (EBV) was the most prevalent finding among herpesviruses detected in children with post-COVID-19 sequela - it was detected in 44 (61.1%) cases. Human herpesvirus (HHV) 6 and cytomegalovirus (CMV) were less common in this group and found in 41 (56.9%) and 30 (41.7%) children, respectively. HHV-1 and HHV-2 were detected more rarely - in 11 (15.3%) children. Monoinfection was diagnosed in 41 (56.9%) cases and a combination of viruses was found in 31 children, in 22 (71.0%) of them it comprised two viruses, in 6 (19.3%) - three viruses, and in 3 (9.7%) - four viruses. The presence of herpesvirus infections underpinned the main reasons why parents of the ill children were seeking for outpatient care, in particular: a prolonged subfebrile condition (18.0%), fatigue and sleep disorders (27.7%), rashes (16.6%), lymphadenopathy (16.7%), ENT diseases (33.3%), more frequently occurring respiratory diseases (33.3%), and the increase in seizure activity in children with epilepsy (8.3%). In addition to herpes viruses, pathogenic agents were detected in 18% of patients, including intracellular pathogens, which were found in 13.9% of 72 children. Taking into consideration the obtained results and established clinical diagnoses, the authors conducted a review and provided a rationale for the administered drug therapy, including medications for herpes treatment. Conclusion: a prior COVID-19 infection induces immunosuppression and, as a result, the activation of herpesvirus infections as long-term effects of COVID-19 (post-COVID conditions). The presence of mixed viral and bacterial pathogens is an indication for administering antivirals, immunomodulators, antibacterial agents, and probiotics. Keywords: post-COVID conditions, herpesvirus infections, children, clinical symptoms, treatment. For citation: Savenkova M.S., Sotnikov I.A., Afanasieva A.A. et al. Importance of herpes viruses in children with post-COVID conditions. Russian Journal of Woman and Child Health. 2023;6(1):39-44 (in Russ.). DOI: 10.32364/2618-8430-2023-6-1-39-44.